Combination of conservative and surgical methods in the treatment of giant lymphedema of the scrotum: A case report - Istranov, Andrey L.; Makarov, Ivan G.; Makarova, Natalya V.; Tulina, Inna; Ulasov, Ilya V.; Isakova, Yuliya I. (Frontiers in Surgery, 2023)
Objective: Genital lymphedema is a severe, disabling condition associated with a malfunction of the lymphatic system. Primary lymphedema of the scrotum is a variant of congenital dysplasia of lymphatic vessels. Secondary genital lymphedema is much more common and can be caused by parasitic invasion (filariasis) or damage to the lymphatic system during the treatment of cancer (radiation therapy, lymphadenectomy). Healthcare providers are frequently unable to detect and treat this illness successfully in ordinary clinical practice. This paper uses the case of a patient with stage 3 secondary lymphedema (unknown genesis) of both lower extremities and lymphedema of the scrotum, complicated by recurrent erysipelas, a history of lymphorrhoea, impaired skin trophic, and multiple papillomatosis, to demonstrate the efficacy of a combination of conservative and surgical methods in the treatment of giant lymphedema of the scrotum. Methods: In the treatment, the combination of decongestant physical therapy (CDPT, CDT) according to M. Földi was used at pre-surgery and post-surgery stages, combined with a reconstructive operation, including the removal of the affected tissues of the urogenital region, phalloplasty, and scrotoplasty with rotational skin flaps. Results: A decrease in the circumference of the lowestr extremities in the lower leg area by 68 cm on the right and by 69 cm on the left was achieved by conservative treatment. Due to the combination of conservative and surgical treatment, the patient’s body weight decreased by 69.4 kg, and the scrotum decreased by 63 cm. Subsequently, the patient fully recovered his sexual function. Conclusions: A combination of complex decongestive physical therapy and surgery isis necessary for patients with advanced genital edema. The isolated use of surgical or conservative treatment does not provide a sufficient improvement in the patient’s quality of life. Modern plastic surgery technologies enable patients to achieve complete functional and cosmetic recovery, while proper selection and usage of compression hosiery help preserve and improve the outcomes acquired following treatment.